On the identity of Carduus euboicus (Asteraceae) from Mt Dirphys, Evvia, Greece - Tan, Kit; Zografidis, Aris (Phytotaxa, 2014)
Carduus euboicus is shown to be a distinct species well-separated from other Greek species of the genus by its skeletal habit with few and reduced leaves, greyish-winged stem, depressed-globose solitary capitulum with short involucral bracts and compressed achenes with a ± sessile pentagonal apical prominence. It bears some morphological similarity to the Balkan endemic C. candicans as well as C. litigiosus from Italy and France but is not closely related to either. It is the sole Greek endemic of the genus being restricted to Mts Dirphys and Xirovouni on the island of Evvia but has been treated as a form of C. nutans in the recently published checklist of the Greek flora.